STRATEGI PENGELOLAAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA DOSEN DI POLITEKNIK ALKON KALIMANTAN - Muhammad Adenuddin Alwy (CV. Lafadz Jaya, 2025)
This study aims to analyze the factors influencing the performance of lecturers at Politeknik Alkon Kalimantan. Through interviews with lecturers and management, the research identifies three main factors contributing to lecturers' performance: intrinsic motivation, management support, and a conducive work environment. The findings indicate that intrinsic motivation drives lecturers to commit and innovate in teaching, while adequate management support enhances lecturers' sense of appreciation and motivation to excel. Additionally, a positive work environment contributes to a supportive atmosphere for lecturers' performance. These findings provide valuable insights for the development of human resource management strategies in higher education institutions.